PERCEPTION AND NEEDS ANALYSIS OF DEVELOPMENT POEM TEACHING MATERIALS BASED ON LOCAL WISDOM - ZAHRA ALWI (Sriwijaya University Learning and Education International Conference, 2016)
This article is a part of the research and development that aims to produce poem teaching materials based on the local wisdom for IX grade of MTs in Palembang in the form of modules and CD. The problem is how are the perceptions and expectations that needed by students and teachers about the material that will made. This study uses the procedures of Bolg & Gall and Jolly & Ballito. The subject of this research are the students and teachers on the IX grade of MTs in Palembang with academic year 2015/2016, one state MTs and two private MTs. Collecting data using documentation, surveys, interview, observations, questionnaires, and focus group discussions. Data analysis using quantitative and qualitative approaches. The results showed: 1) In the curriculum, it is a competence to understand the poem. In the textbook there was only a few materials about poem, no special book that talks about poem, no special literary of teaching materials about poem, poem examples that provided from outside, and learning activities doesn't compatible with the demands of SK and KD. 2) Teachers and students perception's data towards the poem teaching materials used, 87% of teachers and 88% of students stated that poem teaching materials used in schools is not appropriate. 3) Analysis of the poem teaching materials should be developed data is 95.9% of teachers and 85.7% of students claimed it’s a good thing that poem teaching materials develops in the module and CD form. Based on the results of forum group discussions (FGD) concluded that the existing poem teaching materials is not suitable with the curriculum, students are required to have competence in understanding poem. Poem as a literary work that has dulce et utile, contains the values of local wisdom that can be used to increase positive values for the students. The results is perceptions and needs analysis can be used as input for the developmentof poem teaching materials. Teaching materials that will be developed, expected to preserve the localwisdom and useful for the cultivation of moral values which identical to the value of character education.